Lack of full CD8 functional restoration after antiviral treatment for acute and chronic hepatitis C virus infection. Issue 7 (15th February 2012) - Missale, Gabriele; Pilli, Massimo; Zerbini, Alessandro; Penna, Amalia; Ravanetti, Lara; Barili, Valeria; Orlandini, Alessandra; Molinari, Atim; Fasano, Massimo; Santantonio, Teresa; Ferrari, Carlo
Abstract : Background: Hepatitis C virus (HCV) persistence is associated with impaired CD8 functions. Whether functional restoration of CD8 T cells chronically exposed to antigen can be obtained once the antigen is removed remains to be clarified. Objective: To determine whether clearance of HCV by antiviral treatment can fully restore the antiviral function of HCV-specific CD8 cells. Design: Peripheral blood HCV-, Flu- and cytomegalovirus (CMV)-specific CD8 cells were quantified by tetramer staining in 28 patients whose HCV infection resolved after peginterferon or peginterferon/ribavirin treatment for either acute or chronic hepatitis and in eight subjects with acute HCV infection which resolved spontaneously for comparison. HCV-specific CD8 cells were evaluated for their phenotypic and functional characteristics by comparing different patient groups and CD8 cells with different viral specificities in the same patients. Results: Sustained viral response (SVR) did not lead to full maturation of a functional memory CD8 cell response. In particular, SVR in chronic infection was associated with a greater level of T cell dysfunction than responders after acute infection, who showed HCV-specific CD8 responses comparable to those of spontaneous resolvers but weaker than those of Flu-specific CD8 cells. Higher programmed death (PD)-1 expression was detected on HCV than on Flu- and CMV-specific CD8 cells and the effect of PD-1/PD-L1 blockade was better in SVRs after chronic than after acute HCV infection. Conclusion: A better restoration of HCV-specific CD8 function was detectable after SVR in patients with acute hepatitis than in those with chronic disease. Thus, the difficulty in achieving a complete restoration of the antiviral T cell function should be considered in the design of immunomodulatory therapies.